2005
DOI: 10.1002/cphc.200400630
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transfer in Single‐Molecule Photonic Wires

Abstract: Molecular photonics is a new emerging field of research around the premise that it is possible to develop optical devices using single molecules as building blocks. Truly technological impact in the field requires focussed efforts on designing functional molecular devices as well as having access to their photonic properties on an individual basis. In this Minireview we discuss our approach towards the design and single-molecule investigation of one-dimensional multimolecular arrays intended to work as molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 49 publications
0
52
0
Order By: Relevance
“…One major motivation was the elaboration of artificial analogues of the light-harvesting complexes of photosynthetic organisms. [1][2][3][4][5][6][7] However, multichromophoric molecules have also been developed for other applications such as, for example, molecular wires, 8,9 single photon sources, 10 logic gates, 11 light stabilizers, 12 fluorescent DNA probes, 13,14 or nonlinear optical materials. 15 The covalent bonding allows the degree of interaction between the chromophoric units to be controlled to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…One major motivation was the elaboration of artificial analogues of the light-harvesting complexes of photosynthetic organisms. [1][2][3][4][5][6][7] However, multichromophoric molecules have also been developed for other applications such as, for example, molecular wires, 8,9 single photon sources, 10 logic gates, 11 light stabilizers, 12 fluorescent DNA probes, 13,14 or nonlinear optical materials. 15 The covalent bonding allows the degree of interaction between the chromophoric units to be controlled to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…Alternating laser excitation has been applied to achieve fluorescence-aided molecule sorting and enable simultaneous analysis of biomolecular structure and interactions at the level of single molecules by spFRET (81). FRET efficiency could be measured for a DNA-based photonic wire (82,83). The ATP-waiting conformation of rotating F 1 -ATPase has been revealed by spFRET (84).…”
Section: Single-pair Fluorescence Resonance Energy Transfermentioning
confidence: 99%
“…This concept may be extended with the use of several jumper dyes to form "photonic wires" capable of transporting energy over large molecular distances [86]. Garcia-Parajo et al studied such a system composed of five distinct fluorophores placed along a double-stranded DNA molecule from the bluest at one end to the reddest at the other end [87]. Single-molecule fluorescence spectroscopy showed that these systems exhibited complex fluctuations in FRET rates due to dye blinking and spectral and/or orientational fluctuations.…”
Section: 41mentioning
confidence: 99%